PRINCIPLES AND TACTICS FOR DENTAL TREATMENT IN PULMONARY TUBERCULOSIS PATIENTS - Zeynalova, H.V. (World of Medicine and Biology, 2012)
A comprehensive clinical, radiographic, morphologic, immunologic, and direct microscopic examination of dental system have conducted in 150 persons aged 18-55 years and older with a long duration of illness. Among the surveyed patients were male 55,2%, female – 44,8%. The results showed that the tuberculous lesions of the mouth and the entire dentition is seen as a manifestation of the general tuberculous infection, so treatment should be integrated with the patient's general condition and continue by hygienic, therapeutic and other interventions.
Keywords: caries; tuberculosis; treatment